Green synthesis of zinc oxide nanoparticles using Peristrophe bicalyculata (Retz.) Nees leaf extract: Characterization and anti-bacterial activity (International Journal of Pharmaceutical Sciences and Drug Research, 2025)
Nanotechnology has developed as a key part of investigation in modern-day material science in recent decades. Biosynthesized nanoparticles garnered substantial significance due to their accelerated synthesis, economic viability and environmentally benign characteristics. The current study uses Peristrophe bicalyculata (Retz.) Nees leaf extract to produce ZNO NPs in an ecologically safe manner. These nanoparticles were created using zinc acetate dihydrate utilizing extract of leaves as biological reductant. Created nanoparticles were evaluated using UV-Visible (UV-VIS) spectroscopy. Characteristics of produced nanoparticles and their constituent elements were analysed through XRD (X-ray diffraction). The ZNO NPs exhibited crystalline morphology. According to SEM imaging, the ZNO NPs appeared to possess a non-uniform spheroid morphology. The functional groups involved in capping along with reduction processes were identified using Fourier transform infrared (FTIR) spectroscopy. Efficacy of ZNO-NPs may be associated with their size and shape as observed through scanning electron microscope (SEM) as well as transmission electron microscope (TEM). Our investigation assessed efficiency of ZNO-NPs as potent bactericidal agents against Echerichia coli, Staphylococcus aureus, Salmonella typhi, Bacillus subtilis, Bacillus megaterium, Bacillus albus and Streptococcus pneumoniae. This study demonstrates that zinc oxide nanoparticles synthesized via a green approach possess intrinsic antibacterial efficacy, supporting their potential application in the development of antimicrobial therapeutics. Additional studies are essential to explore the mechanistic pathways and determine the cytotoxicity of zinc oxide nanoparticles.